Internal Carotid Artery Stenosis Presenting with Limb Shaking TIA - Awad Javaid; Mostafa Alfishawy (Case Reports in Neurological Medicine)
Internal carotid artery (ICA) stenosis may lead to a wide range of clinical symptoms. We describe the case of a 66-year-old female who experienced a transient ischemic attack (TIA) with episodes of limb shaking caused by ICA stenosis. After epilepsy had been suspected and ruled out, studies of her left ICA showed extensive blockage as a result of atherosclerosis. Magnetic resonance angiography (MRA) revealed total occlusion of the left ICA and the patient was eventually medically managed due to the strong possibility of surgical complications. We reported this patient’s clinical course to shed light on a rare manifestation of carotid stenosis that may be confused with other diagnoses if not closely scrutinized.